State secrecy and security : refiguring the covert imaginary - Walters, William, 1964- (Abingdon, Oxon ; New York : Routledge, 2021)
"In State Secrecy and Security: Refiguring the Covert Imaginary, William Walters calls for secrecy to be given a more central place in critical security studies and elevated to become a core concept when theorizing power in liberal democracies. Through investigations into such themes as the mobility of cryptographic secrets, the power of public inquiries, the connection between secrecy and place-making, and the aesthetics of secrecy within immigration enforcement, Walters challenges commonplace understandings of the covert and develops new concepts, methods, and themes for secrecy and security research. Walters identifies the covert imaginary as both a limit on our ability to think politics differently, and a ground to develop a richer understanding of power"--
Introduction: secrecy, security, and the covert imaginary -- Deciphering Venona: time, space, and the mobilization of secrecy -- On Orford Ness, an island full of national secrets -- The 9/11 commission: secrecy and public inquiry -- Anti-deportation: migration and the aesthetics of secrecy.
OCLC-licensed vendor bibliographic record.
Keywords: Official secrets; National security; Cryptography; Security classification (Government documents); POLITICAL SCIENCE / General; POLITICAL SCIENCE / International Relations / Diplomacy; POLITICAL SCIENCE / Political Freedom & Security / International Security